FILOSOFI TIRAKAT DAN KONSEP TAWAKKAL SEBAGAI STRATEGI RESILIENSI PENGUSAHA KECIL MUSLIM DI YOGYAKARTA: The Philosophy of Tirakat and the Concept of Tawakkul as Resilience Strategies of Muslim Small Entrepreneurs in Yogyakarta - Carolina Ety Widjayanti (tesco publisher, 2025)
This study aims to empirically test the influence of the practice of the Tirakat philosophy and the concept of Tawakkal on the business resilience of Muslim small business owners in Yogyakarta amid economic uncertainty. Using a quantitative explanatory approach, this study involved 150 micro- and small-business owners selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression in SPSS. The results showed that the Tirakat philosophy has a positive and significant effect on business resilience. This indicates that the practice of self-discipline and concern strengthens entrepreneurs' mental resilience. Similarly, the concept of Tawakkal was found to have a significant positive effect on resilience, where the level of active submission to God provides crucial inner peace when facing a crisis. Together, these two variables accounted for 58.4% of the business resilience variable, with the remainder influenced by other external factors. These findings confirm that, for Muslim entrepreneurs in Yogyakarta, resilience strategies are derived not only from material and managerial aspects but also from deeply rooted local spiritual and theological values. The integration of hard work through Tirakat and surrender through Tawakkal has proven an effective coping mechanism for maintaining business continuity amid economic pressure.